Implementation of Enterprise Risk Management in Medium-Sized Priority Sector Companies in East Java - Pwee Leng; Basuki Basuki; Rahmat Setiawan (Institute of Research and Community Outreach - Petra Christian University, 2022)
Enterprise Risk Management (ERM) has the benefit of enhancing organizational effectiveness, risk reporting, and improving business performance. The maturity measurement of ERM implementation is crucial in deducing risk management conditions and disparities within the company as means to achieve a more targeted ERM pursuance, one which is beneficial in assessing the company's condition. This study used sixteen criteria of ERM Maturity Models, to measure the maturity level of ERM implementation carried out by medium-sized industrial companies in priority sectors in East Java. Data were obtained from 137 company directors or managers of Medium Industry companies dispersed across 38 districts/cities in East Java among 6 priority sectors. Results showed that 43.5% and 46.6% of companies that experienced sales growth and an increase in net profit, respectively, are companies with optimal implementation of ERM. Meanwhile, 67% of companies that underwent a decline in sales performance and net profit turned out to be companies with weaker ERM implementation levels.